2005
DOI: 10.1079/phn2005805
|View full text |Cite
|
Sign up to set email alerts
|

Review of the evidence linking protein and energy to mental development

Abstract: Objective: To examine the evidence as to whether the relationship between undernutrition and poor child development is causal. Design: Selected studies from developing countries were discussed. Observational studies were first considered then experimental studies of preventative and remedial supplementation. The type of functions affected, the presence of sensitive periods and the role of protein and energy versus that of micronutrients were reviewed. Results: Childhood undernutrition is generally associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 64 publications
3
69
0
5
Order By: Relevance
“…85,86 A few trials of energy supplementation have also indicated improved cognitive development for undernourished children or those at high risk of malnutrition. [87][88][89] Our finding that linear growth in the first 2 years of life appears to be a stronger independent predictor of both early and later childhood cognition as compared with growth after 2 years of age also corroborates a growing body of neuroscientific research showing that exposure to environmental and biological adversity during early sensitive periods of brain development can be particularly detrimental to cognitive development. 90 We found a significantly muted cross-sectional association of HAZ with cognition for children .2 years old.…”
Section: Figuresupporting
confidence: 68%
“…85,86 A few trials of energy supplementation have also indicated improved cognitive development for undernourished children or those at high risk of malnutrition. [87][88][89] Our finding that linear growth in the first 2 years of life appears to be a stronger independent predictor of both early and later childhood cognition as compared with growth after 2 years of age also corroborates a growing body of neuroscientific research showing that exposure to environmental and biological adversity during early sensitive periods of brain development can be particularly detrimental to cognitive development. 90 We found a significantly muted cross-sectional association of HAZ with cognition for children .2 years old.…”
Section: Figuresupporting
confidence: 68%
“…Over 40-60 % of childhood deaths from diarrhoea, pneumonia, malaria and measles in Africa have been attributed to undernutrition (4) and over 50 % of in-patient hospital admissions and deaths in Kenya were ascribed to malnutrition (5) . Early childhood stunting has been associated with long-term cognitive, motor and behavioural deficits including lower levels of intelligence, attention deficits, poor school achievement, impaired fine motor function and social skills, and low work capacity (6,7) . While previous research studies have helped to identify a number of determinants of child undernutrition in Kenya and other low-income nations (8)(9)(10) , most studies often approach the under-5s as a single group of children.…”
mentioning
confidence: 99%
“…Cross-sectional studies have linked stunting (short stature for age) and low weight-for-age to poor development and school achievement in infants and children (2) . The detrimental effects of undernutrition early in life (, 2 years of age) on intellectual development seem irreversible and remain apparent during childhood and adolescence (3,4) .…”
mentioning
confidence: 99%